2018
DOI: 10.1038/s41598-018-29894-6
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Buffalo nasal odorant-binding protein (bunOBP) and its structural evaluation with putative pheromones

Abstract: In addition, in the Supplementary file 'Figure S1 S2 S3 Table S1 S2' , the Present Addresses for the authors Ramu Muthu Selvam and Mohammad Abdulkader Akbarsha were omitted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In our study, we conducted an RMSD analysis to gauge the conformational flexibility of these complexes, which revealed interesting findings . The RMSD of six ligands with buffalo nasal OBP (bunOBP) attained equilibrium at around three ns and remained relatively constant throughout the simulation, suggesting that bunOBP binds to the odors (ligands) and facilitates sexual communication in buffalo . However, it is worth noting that we observed highly fluctuating RMSD values for some of the protein–ligand complexes during the simulation.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In our study, we conducted an RMSD analysis to gauge the conformational flexibility of these complexes, which revealed interesting findings . The RMSD of six ligands with buffalo nasal OBP (bunOBP) attained equilibrium at around three ns and remained relatively constant throughout the simulation, suggesting that bunOBP binds to the odors (ligands) and facilitates sexual communication in buffalo . However, it is worth noting that we observed highly fluctuating RMSD values for some of the protein–ligand complexes during the simulation.…”
Section: Discussionmentioning
confidence: 86%
“…However, other quinoline complexes (pheromaxein–quinoline, SAL–quinoline, and VEGP–quinoline) showed higher energy values, suggesting that quinoline may be less effective in binding with pheromaxein, SAL, and VEGP compared to the steroidal ligands. In other studies, ligand-binding assays have revealed high-affinity interactions, such as the binding of oleic acid and p-cresol with buffalo nasal OBPs and lauric acid with Fel d1. , The docking score of p-cresol with β-lactoglobulin and OBP revealed the high-affinity binding of p-cresol with OBP . It is not surprising that p-cresol is an estrus-specific pheromone identified in many body fluids. Docking of mice pheromones (farnesol and 2-isobutyl-3-methoxypyranize) with estrus urinary lipocalin protein revealed high binding energy .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pheromone-binding OBPs in body fluids and odor-binding OBP in nasal mucus are identical in structure, although they may have different chemical and physiological properties. They can be found in the epithelium but at low concentrations [11].…”
Section: Discussionmentioning
confidence: 99%